La justice pénale malgache : entre l'héritage colonial et le droit au procès équitable - Randriamahefarilala, Rindra (Université de Montpellier, 2021)
La Justice pénale est un champ de confrontation de plusieurs acteurs qui se concurrencent pour s’accaparer les pouvoirs répressifs. La colonisation de Madagascar par la France date de 1896 à 1960. Pendant l'occupation de Madagascar, les administrateurs français ont subtilisé ces pouvoirs des mains des juges malgaches. La population est soumise à une organisation judiciaire discriminatoire. La justice pénale indigène applique une procédure violente et expéditive. Le gouverneur général et le procureur général détiennent des pouvoirs judiciaires exorbitants et gèrent la carrière des magistrats. Le pouvoir exécutif asservit la justice. Les droits de l'Homme sont dans les discours de justification de la colonisation mais ils sont violés dans les territoires coloniaux. Le détournement des droits de l’Homme, dont le droit au procès équitable, est à la base de la politique d’exploitation. La période néocoloniale et les années socialistes maintiennent un héritage colonial pesant. La justice reste impuissante et désordonnée. La couverture judiciaire est insatisfaisante. L'organisation judiciaire coloniale et la procédure expéditive des juridictions indigènes sont entérinées dans la nouvelle République. Le rajustement ne s’opère que dans les années quatre-vingt-dix où les pouvoirs répressifs basculent vers les magistrats et les citoyens au détriment de l’Exécutif. Le droit au procès équitable évince progressivement cet héritage. L'indépendance et l'impartialité des magistrats deviennent des principes constitutionnels assortis de garanties. La notion de délai raisonnable du procès reçoit également une consécration. Les atteintes provisoires à la liberté sont strictement encadrées. Toutefois, les acquis restent précaires. Les pouvoirs répressifs sont rajustés mais ils restent fragilisés par le statisme du pouvoir du citoyen de se faire rendre justice et par l’éclatement du pouvoir du magistrat de rendre cette justice. La Justice malgache d’aujourd’hui demeure une justice à améliorer, elle est encore perçue comme une Justice injuste.
Keywords: Colonisation; Colonization; Criminal justice; Criminal law; Droit au procès équitable; Droit pénal; Judge; Juge; Justice pénale; Madagascar; Procès équitable; Right to a fair justice

La rénovation du contrôle exercé par l’autorité judiciaire sur la phase préparatoire du procès pénal - Gio, Pierre (Université de Strasbourg, 2021)
La phase préparatoire du procès pénal, qui comprend l’enquête de police et l’instruction préparatoire,consiste à mettre les affaires en état d’être jugées. Compte tenu des atteintes qui sont susceptibles d’êtreportées aux libertés individuelles à ce stade, il est important que le contrôle de l’autorité judiciaire soit le pluseffectif possible. Or ce dernier souffre d’insuffisances et de limites. Afin d’y remédier, il paraît indispensablede commencer par renoncer à l’information judiciaire. Compte tenu de l’expansion de la phase policière et dela mise en avant constante du juge des libertés et de la détention, le maintien de la distinctionenquête/instruction ne paraît plus justifié. Les nombreux bienfaits de l’instruction préparatoire devrontnéanmoins être maintenus au maximum. S’il n’est guère concevable de juridictionnaliser le futur cadred’enquête, l’action publique n’étant pas encore exercée à ce stade, il est possible de procéder à sajudiciarisation en renforçant considérablement les droits des justiciables ainsi que le rôle des juges. Aussi estilproposé de consacrer de façon maîtrisée le contradictoire et ses corollaires (accès au dossier, à l’avocat,possibilité de solliciter des actes…), via la création des statuts de « suspect » et de « victime ». Il est égalementnécessaire d’accroître les garanties statutaires des magistrats du ministère public et d’articuler le cadre rénovéet désormais unique de la mise en état autour d’un double degré de juridiction : le juge de l’enquête et deslibertés au premier degré, la chambre de l’enquête et des libertés au second degré. Ces deux juridictionsseront chargées de veiller à la bonne marche des investigations et de contrôler les atteintes les plus gravesaux droits et libertés.
Keywords: Autorité judiciaire; Control; Contrôle; Enquête de police; Enquêtes criminelles; Indépendance judiciaire; Instruction préparatoire; Judicial authority; Liberté provisoire; Mise en état des affaires pénales; Phase préparatoire du procès pénal; Policy enquiry; Pre-trial phase of proceedings; Preliminary investigation; Preparatory stage of criminal proceedings

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments